A single robust stability-indicating RP-HPLC analytical tool for apigenin quantification in bulk powder and in nanoliposomes: a novel approach - Priya Shetti; Sunil S. Jalalpure (SpringerOpen, 2021)
Abstract Background Apigenin (4', 5, 7-trihydroxyflavone), a flavonoid, is present usually in fruits and vegetables possessing numerous biological properties like antioxidant, anti-viral, antibacterial, anti-inflammatory, and chemoprevention activity. So present study was aimed to prepare and characterize nanoliposomes of apigenin and estimate its encapsulation efficiency by stability-assisted reverse-phase (RP)-HPLC method. Results The stability indication of the RP-HPLC method developed for apigenin-loaded nanoliposomes was successfully demonstrated and parameters were mainly the retention time which was 4.21 min, limit of detection (LOD) 0.49 μg/mL, limit of quantification (LOQ) 1.48 μg/mL, and %relative standard deviation (RSD) less than 2%. Therefore, the stability indication of the developed reverse-phase HPLC method for apigenin-loaded nanoliposomes was demonstrated successfully and parameters like accuracy, linearity, LOD, LOQ, precision, and %RSD were within the limit range and found to be satisfactory. Conclusion The developed RP-HPLC method was found to be suitable for the quantification or estimation of apigenin with its stability in apigenin-loaded nanoliposomes, and this method will be a powerful tool in the future for the estimation of apigenin present in any pharmaceutical preparations.